RADIATION THERAPY IN MEDICINE (Web of Discoveries: Journal of Analysis and Inventions, 2023)
The work examines all types of radiation therapy that are used in modern medicine. The purposes and medical purposes of all types of radiation therapy and ionizing devices are given.